Participatory action research experiences for undergraduates: forging critical connections through community engagement. Issue 11 (1st November 2020) - Trott, Carlie D.; Sample McMeeking, Laura B.; Weinberg, Andrea E.
ABSTRACT: Embedded within ongoing university-community partnerships, participatory action research experiences for undergraduates – or PAR-based UREs – are multi-disciplinary, action-oriented research opportunities that engage undergraduates in collaborative research to address community-defined challenges. PAR-based UREs integrate participatory action research (PAR), a practice of social scientists, with undergraduate research experiences (UREs), a widespread and well-funded tradition in STEM (science, technology, engineering, and mathematics) fields. PAR-based UREs offer a promising avenue towards fostering constructive university-community relations, while positioning undergraduate students to be competent researchers and critical change agents in collaboration with communities. This theoretical discussion introduces the concept and practice of PAR-based UREs by: (1) reviewing 'traditional' PAR and URE arrangements as separate entities; (2) offering a theoretical rationale for their integration; and (3) describing the formation, organization, and outcomes of a PAR-based URE pilot program, which underscores the need for a coordinated approach towards benefiting – and reconnecting – students, communities, universities, and the public.